Interleukin-17A Facilitates Chikungunya Virus Infection by Inhibiting IFN-α2 Expression - Neupane, Biswas; Acharya, Dhiraj; Nazneen, Farzana; Gonzalez-Fernandez, Gabriel; Flynt, Alex Sutton; Bai, Fengwei (Frontiers in Immunology, 2020)
Interferons (IFNs) are the key components of innate immunity and are crucial for host defense against viral infections. Here, we report a novel role of interleukin-17A (IL-17A) in inhibiting IFN-α2 expression thus promoting chikungunya virus (CHIKV) infection. CHIKV infected IL-17A deficient (Il17a-/-) mice expressed a higher level of IFN-α2 and developed diminished viremia and milder footpad swelling in comparison to wild type (WT) control mice, which was also recapitulated in IL-17A receptor-deficient (Il17ra-/-) mice. Interestingly, IL-17A selectively blocked IFN-α2 production during CHIKV, but not West Nile virus (WNV) or Zika virus (ZIKV), infections. Recombinant IL-17A treatment inhibited CHIKV-induced IFN-α2 expression and enhanced CHIKV replication in both human and mouse cells. We further found that IL-17A inhibited IFN-α2 production by modulating the expression of Interferon Regulatory Factor-5 (IRF-5), IRF-7, IFN-stimulated gene 49 (ISG-49), and Mx1 expression during CHIKV infection. Neutralization of IL-17A in vitro leads to the increase of the expression of these antiviral molecules and decrease of CHIKV replication. Collectively, these results suggest a novel function of IL-17A in inhibiting IFN-α2-mediated antiviral responses during CHIKV infection, which may have broad implications in viral infections and other inflammatory diseases.